Failure of hormonal contraceptive methods in Brazilian woman: A literature review (Research, Society and Development, 2023)
Introduction: The use of hormonal contraceptive methods is one of the most common ways to prevent pregnancy in Brazil and in the world. Despite the effectiveness of these methods, contraceptive failure is still a concern for many women. Data shows that the rate of hormonal contraceptive failure in the country is still high, which can lead to unplanned pregnancies and affect women's reproductive health. In this context, it is important to understand the factors that influence the effectiveness of these methods and seek more effective alternatives to avoid unwanted pregnancy. Objective: This review aims to explore the failure rate of hormonal contraceptive methods in Brazilian women and discuss the possible reasons for this failure. Methods: This is a narrative review of the literature on the theme "Failure of hormonal contraceptive methods in Brazilian women: a literature review", having as source the databases PubMed, Google Scholar, Web of Science, Scopus, Scielo and BVS. Publications between 2006 and 2023 were included. All articles selected for the study were prepared in English and Portuguese. Results: Results show that the failure in the efficacy of contraceptive methods is mainly related to the incorrect use of the contraceptive of choice. Conclusion: Despite the high rate of use of hormonal contraceptive methods by Brazilian women, the rate of unplanned pregnancies is still high in the country, and efective measures are needed to minimize the risk of contraceptive failure.